Promoter Specificity and Efficacy in Conditional and Inducible Transgenic Targeting of Lung Macrophages - McCubbrey, Alexandra L.; Allison, Kristen C.; Lee-Sherick, Alisa B.; Jakubzick, Claudia V.; Janssen, William J. (Frontiers in Immunology, 2017)
Conditional and inducible Cre-loxP systems are used to target gene deletion to specific cell lineages and tissues through promoter-restricted expression of the bacterial DNA recombinase, Cre. Although Cre-loxP systems are widely used to target gene deletion in lung macrophages, limited data are published on the specificity and efficiency of “macrophage targeting” Cre lines. Using R26-stopfl/fl-TdTomato and tetOn-GFP reporter lines, we assessed the specificity and efficiency of four commercially available Cre driver lines that are often considered “macrophage specific.” We evaluated two conditional (Csf1r-Cre and LysM-Cre) and two inducible [CX3CR1-estrogen receptor-Cre (ERCre) and CD68-rtTA] lines. We assessed Cre activation in six resident lung myeloid populations, as well as activation in lung leukocytes, lung epithelial and endothelial cells, peripheral blood leukocytes, and tissue macrophages of the spleen, bone marrow, and peritoneal cavity. Although Csf1r-Cre and LysM-Cre target resident alveolar macrophages (ResAM) and interstitial macrophages (IM) with high efficiency, neither line is specific for macrophages. Csf1r-Cre targets all leukocyte populations, while LysM-Cre targets dendritic cell, neutrophils, monocytes, and a quarter of lung epithelial cells. CX3CR1-ERCre and CD68-rtTA both target IM, but do not target ResAM. Further, although neither line is specific for macrophages, a pulse-wait administration of tamoxifen or doxycycline can be used to significantly improve IM specificity in these inducible lines. In summary, while Cre-loxP remains a powerful tool to study macrophage function, numerous pitfalls exist. Herein, we document strengths and weaknesses of Csf1r-Cre, LysM-Cre, CX3CR1-ERCre, and CD68-rtTA systems for targeting specific macrophage populations in the lungs and provide data that will aid investigators in selecting the proper strain.